Scientific Research Management in Romania - Angelica BACESCU-CARBUNARU; Monica CONDRUZ-BACESCU (Revista de Management Comparat International)
The present paper presents the challenges of scientific research in the Romanian environment. The first part deals with current issues of the Romanian scientific research. After 25 years of searching, scientific research has not found the solution of working in correlation with major rules in EU countries. The change in the Romanian political system in 1990 found society unprepared for research work in the market economy. The second part focuses on how the research system should function. This requires a national management measure, which means the appearance of high professionalism and efficiency structures, made of specialized companies, that should operate on the principle of commissions. The last part presents the research strategy in regional, national and international framework. The conclusion is that the level of innovation and research culture in Romania is low, both in the business sector and in academia. In the field of interaction with the international environment, significant technological gaps in comparison with developed countries, stimulate technology import to the detriment of innovation.